If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -1(2y + -3) = 1 + -3y Reorder the terms: 9 + -1(-3 + 2y) = 1 + -3y 9 + (-3 * -1 + 2y * -1) = 1 + -3y 9 + (3 + -2y) = 1 + -3y Combine like terms: 9 + 3 = 12 12 + -2y = 1 + -3y Solving 12 + -2y = 1 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 12 + -2y + 3y = 1 + -3y + 3y Combine like terms: -2y + 3y = 1y 12 + 1y = 1 + -3y + 3y Combine like terms: -3y + 3y = 0 12 + 1y = 1 + 0 12 + 1y = 1 Add '-12' to each side of the equation. 12 + -12 + 1y = 1 + -12 Combine like terms: 12 + -12 = 0 0 + 1y = 1 + -12 1y = 1 + -12 Combine like terms: 1 + -12 = -11 1y = -11 Divide each side by '1'. y = -11 Simplifying y = -11
| y-7=-1/2(x-4) | | (3x-9i)(x-3i)=0 | | 7(4y+5)=19y+8 | | 2y+y+9y= | | 15y=6y^2 | | a+1+a+3+2a=180 | | 1+3s=4 | | a+1+a+3+2a=90 | | x*y=31 | | 16f=1.8+32 | | c=2a+3 | | m/36=2 | | dxy=31 | | F(x)=-2x^2-5x+7 | | 7(x+5)+5=9x-2(x-4) | | 70=6p+34 | | 16=2a+5 | | 3x+5+6x-9=-4 | | -45=32 | | 4=-7s+53 | | 6b-3b=0 | | 50+d=2d | | 5x+x+20+40=180 | | x+y-12x+8y-8=0 | | 5x-64/9=64 | | 7(4y+5)=19+8 | | -u+2=220 | | w=x(y/z) | | N/0.6=8 | | 6=3a+3 | | 30-x=5x+6 | | -43+x=23-2x |